Strong Men, Strong Communities: Design of a Randomized Controlled Trial of a Diabetes Prevention Intervention for American Indian and Alaska Native Men. Issue 4 (August 2020) - Sinclair, Ka'imi; Carty, Cara; Gonzales, Kelly; Nikolaus, Cassandra; Gillespie, Lucas; Buchwald, Dedra
Type 2 diabetes is a serious global epidemic that disproportionately affects disadvantaged populations. American Indians and Alaska Natives (AIs/ANs) have the highest rates of diabetes in the nation with a prevalence of 14.7% in 2018, more than twice that of non-Hispanic Whites. AI/AN men have the highest prevalence of diagnosed type 2 diabetes (14.5%) compared to non-Hispanic Black (11.4%), non-Hispanic Asian (10.0%), and non-Hispanic White (8.6%) men. Several landmark clinical trials have shown that lifestyle interventions can effectively prevent or delay the onset of diabetes among those at risk, including in AIs/ANs. Despite positive outcomes for AIs/ANs in these studies, very few were men. To date, there have been no concerted efforts to recruit and retain AI/AN men in interventions that promote weight loss and healthy lifestyles to prevent diabetes, and they remain underrepresented in these types of studies. This article describes the design and methods of the first randomized controlled trial of a diabetes prevention program with a study sample comprised entirely of AI/AN men. Research to date has demonstrated suboptimal patterns of recruitment and retention of AI/AN men, resulting in their virtual absence in health and intervention research. Effective methods to recruit and retain AI/AN men, and potential benefit gained from participation in diabetes prevention research, are unknown for this population who experience a high prevalence of type 2 diabetes. The study design presented in this article offers promising insights to help remedy these important shortcomings in the science of recruitment and retention of AI/AN men in research.